Information Technology and communication (IT&C) and Research and Development (R&D), outstanding factors of the post-crisis economic recovery - ZAMAN, Gheorghe; GHERASIM, Zenovic (Annals of Spiru Haret University. Economic Series, 2010)
Regardless of the business cycle or of the crisis, the knowledge-based society continues to evolve based on two main pillars – IT&C and R&D – although the funding and investments in such areas are currently more or less shrinking. Under these circumstances, there are economic, social, technological and environmental reasons for which investments in the IT&C and R&D fields must be prioritized under the anti-crisis strategies in Romania. The main argument in favour of is mainly based on the economic and social efficiency, on the technological progress on short, medium and long terms. At the same time, we are pointing out the main ways, instruments and mechanisms through which efficiency could be obtained for IT&C and R&D investments efforts in Romania during the post-crisis economic recovery.